Turkey’s Accession to the European Union: Does Culture and Identity Play a Role? - Meltem Müftüler Baç; Evrim Taşkın (Ankara Avrupa Çalışmaları Dergisi)
It is a highly acknowledged fact that in the European Union 's enlargementprocess, Turkey plays a highly interesting role and deserves analytical attention interms of its theoretical and policy making implications. This fact has become morepronounced since the start of accession talks with Turkey on 3 October 2005. However,the opening of the Turkish accession talks marked the beginning of a new era in termsof defining what constitutes Europe and the European identity. It is for this reason thatTurkey's accession to the EU should be evaluated within the langer framework of EUenlargement and the European integrati on process and goes beyond an analysis ofbilateral relations. Thus, Turkey's ability to adopt the EU standards is only one aspectof the whole picture with the EU specific factors playing an equally important role. Thispaper argues that the enlargement process of the EU determines the boundaries of whatis Europe and what is not and that Turkey's accession to the EU becomes the mostimportant and visible line of demarcation in that aspect. This means that a candidate 'saccession negotiations to the EU are determined by perceptions of that candidate's fitinto a predetermined European identity. That is why the Turkish case is importantbecause it illustrates the ambivalent nature of Europeanness and attempts by memberstates to clearly define it. The purpose of this article is to analyze to process ofenlargement from the sociological/constructivist approaches with regard toenlargement in general and towards Turkey in particular.